ANALISIS KESIAPAN PENERAPAN DIGITALISASI AKUNTANSI USAHA MIKRO KECIL SEKTOR PARIWISATA DI KABUPATEN MEMPAWAH - Lasari, Tania; Kristiawati, Endang; Afif, Ali (Program Studi Akuntansi Universitas Panca Bhakti, 2023)
This research prioritizes the discussion of how. Readiness to Implement the Digitalization of Accounting for Smalland Medium Enterprises Sector.Tourism in Mempawah Regency which aims to find out how the ReadinessAnalysis for the Implementation of Digitalization of Accounting for Micro Small Businesses in the Tourism Sectorin Mempawah Regency. This study uses a qualitative research method, with data collection techniques that areused, namely carrying out direct observation activities at the research site, interviewing informants, making thenecessary documentation. The data analysis technique used is In-deph Interview. Based on the results of thisstudy, the Preparedness of Digitalization of Accounting for Small and Micro Enterprises in the Tourism Sector inMempawah Regency, namely the two research objects that the researchers examined, namely Pondok Pengkangin Piniti and Jungkat Beach in Jungkat, that currently the two MSME objects have optimism and are willing toinnovate that technology and digital can change their business for the better and don't mind trying new things.However, they still feel overwhelmed in the learning process and feel they do not understand the digitalizationsystem.